Relationship between active inflammatory lesions in the spine and sacroiliac joints and new development of chronic lesions on whole-body MRI in early axial spondyloarthritis: results of the ESTHER trial at week 48. Issue 7 (8th May 2011) - Song, I-H; Hermann, K G; Haibel, H; Althoff, C E; Poddubnyy, D; Listing, J; Weiß, A; Freundlich, B; Rudwaleit, M; Sieper, J
Abstract : Aim: To investigate the relationship between active inflammatory lesions on whole-body MRI (wb-MRI) and new development of chronic lesions on T1 MRI in patients with early axial spondyloarthritis (SpA) treated either with etanercept (ETA) or sulfasalazine (SSZ). Methods: Wb-MRIs of 65 patients treated either with ETA (n=35) or SSZ (n=30) over 1 year were scored for active inflammation, fatty lesions, erosions and ankylosis in the 23 vertebral units (VUs) of the spine and in the sacroiliac joints (SI joints). Scoring was performed by two blinded radiologists. Results: If there was no previous inflammation in the bone no new fatty lesions occurred in SI joint quadrants and only a few (0.6%) in spine VUs. There was a significant relationship between disappearance of inflammation and the appearance of fatty lesions: if baseline inflammation resolved fatty lesions occurred in 10.5% of SI joint quadrants and 17.9% of VUs. If inflammation did not resolve over 1 year, fatty lesions occurred less frequently: 2.4% (SI joint quadrants) and 7.2% (VUs). There was a significantly higher increase of the mean fatty lesion score between baseline and week 48 in the ETA (4.0 vs 4.8 for the SI joints and 1.9 vs 2.7 for the spine) compared to the SSZ (3.0 vs 3.2 for the SI joints and 1.1 vs 1.2 for the spine, respectively) group (p=0.001 and p=0.020 for the differences). No significant changes in the erosion or ankylosis score were observed in any of the two groups during this time. Conclusions: These data indicate that there is a close interaction between inflammation, tumour necrosis factor blockade and the development of fatty lesions in subchondral bone marrow of patients with axial SpA.